PHARMACOLOGICAL MANAGEMENT OF POSTOPERATIVE PAIN - Savić Vujović, Katarina R; Vučković, Sonja; Medić, Branislava; Srebro, Dragana; Jotić, Ana (Medical Research, 2024)
Postoperative pain is a widespread and underestimated problem in Serbia and globally. Numerous studies conducted in countries with advanced healthcare systems have shown that even in the 21st century, postoperative pain is not adequately managed. More than 80% of patients undergoing surgical procedures experience acute postoperative pain, with 75% describing it as moderate, severe, or extreme. Postoperative recovery depends on patient characteristics and factors that facilitate postoperative recovery, including the presence or absence of postoperative complications. The pharmacology of postoperative pain targets pathophysiological mechanisms such as nociception, peripheral sensitization, ectopic activity, and central sensitization. Modern pharmacological management of postoperative pain involves balanced multimodal analgesia. The principle of multimodal analgesia is based on the multifactorial nature and complexity of pain transmission pathways and is defined as the use of various medications or techniques with different mechanisms of action on the peripheral or central nervous system, which can have additive or synergistic effects. Several drug groups are involved in the multimodal approach, each with a specific pathophysiological mechanism of action. The effectiveness of opioid analgesics in treating moderate to severe postoperative pain is achieved due to the lack of a ceiling effect. However, increasing dosage leads to increased side effects. Nonsteroidal anti-inflammatory drugs (NSAIDs), cyclooxygenase-2 inhibitors (COX-2), and systemic steroids reduce the inflammatory component of surgical pain. Systemic and local anesthetics reduce the release of inflammatory mediators,interleukin-(IL-6, IL-1β, and IL-1 receptor antagonist (-1RA)). Gabapentinoids, by binding to the α-2-δ-1 subunit of voltage-gated Cachannels in the central nervous system (CNS), reduce the release of important excitatory neurotransmitters involved in nociception. α-2-agonists, such as clonidine and dexmedetomidine, modulate pain impulse transmission by activating the spinal cord’s presynaptic and postsynaptic α2 receptors. Local anesthetics (e.g. lidocaine) block neural transmission by inhibiting Na channels, thus preventing the transmission of pain stimuli from the periphery to the central nervous system. N-methyl-D-aspartate receptor (NMDA receptor) antagonists, ketamine and magnesium, reduce central sensitization mechanisms.
Keywords: postoperative pain; pharmacological management; drugs